2021
DOI: 10.3390/molecules26185469
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Salinity Gradient Energy Harvesting Devices

Abstract: Harvesting salinity gradient energy, also known as “osmotic energy” or “blue energy”, generated from the free energy mixing of seawater and fresh river water provides a renewable and sustainable alternative for circumventing the recent upsurge in global energy consumption. The osmotic pressure resulting from mixing water streams with different salinities can be converted into electrical energy driven by a potential difference or ionic gradients. Reversed-electrodialysis (RED) has become more prominent among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Osmotic energy harvesting systems realize controlled mixing procedure of solutions of different salinity to recover energies. These two systems have the advantages of being able to be miniaturized 220 as well as being used on a large scale. Though they are not currently in use for electricity production due to many remaining problems, researches of system amelioration are in full development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic energy harvesting systems realize controlled mixing procedure of solutions of different salinity to recover energies. These two systems have the advantages of being able to be miniaturized 220 as well as being used on a large scale. Though they are not currently in use for electricity production due to many remaining problems, researches of system amelioration are in full development.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these systems can be miniaturized to power on-board sensors. 220 Sadeglian et al 221 have developed 5 cm diameter cells which miniaturizes a RED system. An IEM is placed between two reservoirs which contain saline solutions of cupric sulphate of different concentrations.…”
Section: Osmotic Energy Harvestingmentioning
confidence: 99%
“…Covering 71% of the Earth’s total area, the ocean is a huge source of energy, therefore, the study of salinity gradient energy has received increasing attention from researchers all over the world. Salinity gradient energy is a renewable and clean energy, with the largest content coming from ocean energy. Electricity can be generated from the concentration difference between seawater and freshwater, and it is environmentally friendly, as it does not produce any CO 2 emissions .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the conventional fabrication methods, recent studies have also focused on the fabrication and manipulation of structures using novel unconventional methods and materials. For example, nanopore-based membranes were fabricated using 2D-organic/inorganic compounds such as MXene, graphene oxide, and carbon-based materials such as carbon nitrate, enabling the manipulation of the thickness and pore size of the nanostructures as well as their properties. Although these studies demonstrated successful approaches on both fabrication and manipulation of structure characteristics, it is still necessary to develop simple and facile fabrication methods for adjustable nanochannel/nanopore-based structures from the perspective of applicability and accessibility. , …”
Section: Introductionmentioning
confidence: 99%
“…Although these studies demonstrated successful approaches on both fabrication and manipulation of structure characteristics, it is still necessary to develop simple and facile fabrication methods for adjustable nanochannel/nanopore-based structures from the perspective of applicability and accessibility. 19,20 In addition, studying such nanoscale transport phenomena requires the development of novel observation and measurement methods to accurately quantify the ion/mass transport phenomena along nanopores/nanochannels because of their nanoscopic scales and extremely low signal output. 21 chemical signals with high reliability and high sensitivity.…”
Section: ■ Introductionmentioning
confidence: 99%